Identification of Phenyl Alanine Ammonia Lyase Gene Involved in the Synthesis of Anacardic Acid in Anacardium occidentale L. (International Journal of Pharmaceutical Sciences and Drug Research, 2019)
Anacardic acids, a class of medicinally and industrially important phenolic compounds is found in a variety of dicotyledonous families chiefly in Cashew (Anacardium occidentale L). Phenylalanine ammonia-lyase (PAL) shows a dominant role in the biosynthesis of poly phenolic compounds, which are involved in the defense mechanism in harsh environments related to various stimuli. The current study was conducted to find out the presence of anacardic acid in ethyl acetate extract of young leaves of cashew using high performance thin layer chromatography (HPTLC) method and the presence of phenyl alanine ammonia lyase gene also plays a role in the biosynthesis of anacardic acid in young leaves was also confirmed by cDNA synthesis from a cellular mRNA template connected to the polymerase chain reaction (PCR).